2014
DOI: 10.3892/ijo.2014.2737
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death-1 blockade enhances the antitumor effects of peptide vaccine-induced peptide-specific cytotoxic T lymphocytes

Abstract: Novel treatment modalities are required urgently in patients with hepatocellular carcinoma (HCC). A vaccine that induces cytotoxic T lymphocytes (CTLs) is an ideal strategy for cancer, and glypican-3 (GPC3) is a potential option for HCC. Blocking the programmed death-1 (PD-1)/PD-L1 pathway is a rational strategy to overcome tumor escape and tolerance toward CTLs. In the present study, we investigated whether anti-PD-1 blocking antibodies (αPD-1 Ab) enhanced the number of vaccine-induced peptide-specific CTLs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Willimsky et al reported PD-L1 expression in HCC cells and PD-1 expression in CD8 + T cells [33]. Similarly, Sawada et al showed that PD-1 is highly expressed on the CTLs of patients vaccinated with GPC3 [34]. PD-1/PD-L1 expression in tumor was significantly correlated with HCC stage, local recurrence rate and poor prognosis [35].…”
Section: Pd-1mentioning
confidence: 97%
“…Willimsky et al reported PD-L1 expression in HCC cells and PD-1 expression in CD8 + T cells [33]. Similarly, Sawada et al showed that PD-1 is highly expressed on the CTLs of patients vaccinated with GPC3 [34]. PD-1/PD-L1 expression in tumor was significantly correlated with HCC stage, local recurrence rate and poor prognosis [35].…”
Section: Pd-1mentioning
confidence: 97%
“…However, as a consequence of this influx, cells in the tumor microenvironment upregulate PD-L1 resulting in incomplete tumor cell elimination. Furthermore, analysis of PBMCs following administration of a glypcian-3 (GPC3) peptide vaccine in advanced or metastatic HCC revealed a high expression of PD-1 on peptide-specific CD8 + T-cells [84]. Similarly, immunotherapy using Listeria monocytogenes (Lm)-LLO can be improved by reduction of the Tregs and MDSCs, but as it is also associated with the upregulation of PD-L1 on immune cells, in particular macrophages, the use of antibodies blocking the PD-1:PD-L1 axis is justified [85].…”
Section: Concurrent Combination Of Immunomodulatory Antibodies With Vmentioning
confidence: 99%
“…Therefore we employed the combination therapy by using the peptide vaccine and PD-1 blocking antibody. We demonstrated that PD-1/PD-L1 blockade enhanced the anti-tumor effects of peptide vaccines by increasing the immune response of vaccine-induced CTLs [16].…”
Section: Programmed Death-1 (Pd-1) Blockade Enhances the Antitumor Efmentioning
confidence: 89%